Are We in-Sync? Students' Virtual Instructional Experience and Perceived Information Literacy Skills in Time of Pandemic. Issue 4 (29th October 2021) - Yap, Joseph Marmol; Manabat, April Ramos
Abstract: The COVID-19 outbreak has brought a drastic change in the current educational system. While distance learning and online instruction is not really a new concept in the field of education (Kurzman, 2013 ), it has been intensified with the aim of minimizing physical interactions without jeopardizing the quality of knowledge transfer. The emergence of technology has also implicated changes in the information-seeking behavior of students over time (Oliveira & Greenidge, 2020). Online library orientations and virtual one-shot information literacy (IL) sessions have been in place to supplement virtual classroom instructions by teachers (Lierman & Santiago, 2019 ). The Nazarbayev University (NU) Library through its Reference Office took action and managed to implement creative ways to conduct online sessions. This paper documented NU students' virtual library experiences with subject librarians during the pandemic as perceived by students. The 10-item workshop evaluation revealed that students felt very satisfied with the content, coverage, and organization of library sessions. They also highly agreed that the conduct of library sessions was practical, clear, and has an avenue for interaction and development of their IL skills. In a follow-up study with workshop evaluation respondents, a stratified sample size of 101 was determined to identify the current IL skills of students. Students were given the opportunity to conduct a self-assessment of their IL skills. With a 31.68% response rate, the eight-item IL skillset affirmed that students personally believed they were moderate users in searching and evaluating information sources. This paper also determined the frequency of follow-up sessions requested by the students even after attending the online library orientations and IL sessions. Data included in this research was gathered between August 17 to November 27, 2020. To investigate further, an analysis of the reference queries received during the Fall 2020 semester using Reference Analytics was conducted.